Bacteriological Analysis of Groundwater of Karachi (Biological Sciences - PJSIR, 2007)
The  leve l  of  microbial  contami nation  i n  open  we l l s  i n  sel ected  areas  of the  Karach i  ci ty  was  stud i ed  i n consideration  of  the  heal th  of  th e  i n h abi tants  of  the  areas.  A  total  of  1 1 5  we l l  water  sampl es  were  col l ected  and exam i n ed for total  bacteri a l  count and  counts of col ifonn, faecal col iform and Pseudomonas  aeruginosa. The micro biological anal ys i s y ielded presence of col i form and  faecal col iform i n 66.63% and 60. 89% of the samples exam i ned, respecti vel y, w h i le, Pseudo111011as  aeruginosa  was detected  i n 30% of the ground water sam pl es. 84.34% of the water sampl es were found  u n sat i sfactory as per W HO standard s.